Development and evaluation of a fish feed mixture containing the probiotic Lactiplantibacillus plantarum prepared using an innovative pellet coating method - Chomová, Natália; Pavloková, Sylvie; Sondorová, Miriam; Mudroňová, Dagmar; Fečkaninová, Adriána; Popelka, Peter; Koščová, Jana; Žitňan, Rudolf; Franc, Aleš (Frontiers in Veterinary Science, 2023)
Due to the intensification of fish farming and the associated spread of antimicrobial resistance among animals, but also among humans, it is necessary to find new alternatives in the therapy and in the prophylaxis of diseases. Probiotics appear to be promising candidates because of their ability to stimulate immune response and to suppress the growth of pathogens. The aim of this study was to prepare fish feed mixture with various compositions and based on their physical characteristics (sphericity, flow rate, density, hardness, friability, loss on drying) choose the most suitable one for coating with selected probiotic strain Lactobacillus plantarum R2 Biocenol™ CCM 8674 (new nom. Lactiplantibacillus plantarum). Probiotic strain was examined through sequence analysis for the presence of plantaricin-related genes. Invented coating technology based on a dry coating with colloidal silica followed by starch hydrogel containing L. plantarum was applied on pellets and tested for viability of probiotics during 11-months period at different temperatures (4 °C, 22 °C). The release kinetics of probiotics in artificial gastric juice and in water (pH=2 and pH=7) was also determined. Chemical and nutritional analysis was performed for comparison of quality of control and coated pellets. The results showed gradual and sufficient release of probiotics during 24 hours period from 104 CFU at the time 10 minutes up to 106 at the end of measurement into both environments. Number of living probiotic bacteria was stable during whole storage period at 4 °C (108) and no significant decrease of living probiotic bacteria was observed. Sanger sequencing revealed the presence of plantaricin A and plantaricin EF. Chemical analysis revealed increase of multiple nutrients compared to the uncoated cores. These findings disclose that invented coating method with selected probiotic strain improve nutrient composition and did not worsen any of physical characteristics of pellets. Applied probiotics are also gradually released into the environment and have high survival rate when storing at 4 °C during long-time period. Outputs of this study confirm the potential of prepared and tested probiotic fish mixture for future use in in vivo experiments and in fish farms for prevention of infectious diseases.